Batasan Hibah dalam Perspektif Perlindungan Hak Ahli Waris Menurut Hukum Islam dan KHI - Alif Andi (Al Fuadiy Jurnal Hukum Keluarga Islam, 2026)
The regulation of hibah (inter vivos gifts) in Islamic law is closely connected to the protection of heirs’ rights within the inheritance system. In practice, excessive or discriminatory gifts may undermine the principle of justice guaranteed in Islamic inheritance law. A normative legal approach is applied by examining primary legal sources, including the Qur’an, Hadith, and the Compilation of Islamic Law (KHI), supported by fiqh literature and scholarly journals. The analysis demonstrates that although hibah is a lawful act carried out during the lifetime of the property owner, Islamic law restricts its amount to a maximum of one-third of the estate to prevent harm to heirs. Gifts made during maradh al-maut are legally equated with wills and subject to similar limitations. Articles 210–211 of the KHI also provide a mechanism for recalculating parental gifts to children as inheritance in order to ensure fairness. These limitations reflect an effort to balance individual property rights with family protection and the principle of justice in Islamic law.